The Relationship between family function and hypertension management in Desa Tista, Puskesmas Kerambitan II Work Area. - Dewi, Putu Adi Cahya (E-Jurnal Medika Udayana, 2022)
Background and Purposes : Elderly generally experience physical changes such as the cardiovascular system that causes hypertension. Hypertension is a disease that cannot be cured and will cause damage to arteries in the body, causing complications such as coronary heart disease, stroke and kidney failure if not treated in the long term, but hypertension can be controlled through hypertension management. Strategy to improve hypertension management is through family functions. This study aims to determine the relationship between family function and hypertension management in the elderly. Methods: This type of research is correlational analytic, with a cross sectional approach and purposive sampling technique. The subjects of this study were elderly aged 60 years and over. Statistical test used Spearman Rank Correlation with p value < 0.05. Results: From 46 samples, family function in the elderly were mostly in the good category with a total of 28 respondents (60.9%) and management of hypertension in the elderly were mostly in the good category with a total of 30 respondents (65.2%). Based on the results of statistical tests using Spearman Rank, the results obtained were p value 0.000 <0.05 and the correlation coefficient value was 0.606. Conclusion : There is a significant relationship between family function and hypertension management in Desa Tista, Puskesmas Kerambitan II Work Area.   Keywords : Family Function, Management of Hypertension, Elderly